Creating value : a concise guide for boards and directors - Rainbird, Mark; Walters, David (Australian Institute of Company Directors, 2016)
Provides a framework of basic tools and terminology for understanding and evaluating the various and often confusing measures and concepts surrounding value and its creation and management.